O professor da educação especial e o processo de ensino aprendizagem de alunos com autismo - Lourenço, Ana Carla de [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Autism is the theme of this study and the occurrence of the teaching-learning process of students with autism was observed. The study took place in a special education school. Nowadays, infantile Autism is classified as one of the “Development Global Disorders” and it is characterized by serious and global impairments in several aspects of the development, as the reciprocal social interaction, communication abilities and presence of behavioral stereotypes, interests and activities. Notwithstanding, these subjects present a triad of impairments concerning the development areas, such as: communication incapacity for social interaction and imagination, which affect directly the learning process. Thus, the aim of this study was to identify the teaching methodology employed for children with autism concerning special education and to verify in which aspects this methodology can help the teachinglearning process of those students. For this reason, a specialist teacher and three students with autism, of a special Education School, located in the interior of São Paulo state, took part in this study. For data collection, a total of 19 activities realized by the students with autism were observed inside the classroom. The specialized teacher answered a semi structured interview. The results demonstrated that the specialized teacher does not employ any specific teaching methodology, in order to help the teaching-learning process for those students, although there are some specific methodologies for children with autism, which are employed in special education schools. Nevertheless, it can be observed a lacuna concerning the teaching process employed by the teacher, and some uncertainly referring to the leaning process of those students with autism who attend that school

O presente trabalho tem como tema o autismo, e buscou verificar como ocorre o processo de ensino-aprendizagem de alunos com autismo em uma escola de educação especial. O Autismo infantil é hoje classificado como um dos “Transtornos Globais do Desenvolvimento (TGD)” e é caracterizado por um comprometimento grave e global em diversas áreas do desenvolvimento, como nas habilidades de interação social recíproca, habilidades de comunicação e presença de estereotipias de comportamento, interesses e atividades. Assim, esses indivíduos apresentam uma tríade de comprometimentos com incapacidades em três áreas do desenvolvimento, quais sejam: incapacidade na comunicação, na interação social e na imaginação, as quais afetam diretamente seu processo de aprendizagem. Dessa forma, esse trabalho teve como objetivo identificar a metodologia de ensino utilizada com crianças com autismo na educação especial e verificar em que aspectos essa metodologia auxilia no processo de ensino-aprendizagem desses alunos. Para tal, participou da pesquisa uma professora especialista e três alunos com autismo de uma Escola de Educação Especial localizada no interior do Estado de São Paulo. Para a coleta de dados foram realizadas 19 observações de atividades realizadas pelos alunos com autismo em sala de aula e aplicada uma entrevista semi-estruturada à professora especialista. Os resultados demonstraram que a professora especialista não utiliza nenhuma metodologia de ensino específica para auxiliar no processo de ensino-aprendizagem desses alunos, apesar de existirem algumas metodologias específicas para crianças com autismo, que são empregadas em escolas de educação especial. Assim, verifica-se uma lacuna no processo de ensino por parte da professora e uma incerteza quanto ao processo de aprendizagem desses alunos com autismo, nessa instituição
Keywords: Autismo em crianças; Educação especial; Ensino; Aprendizagem; Autism in children; Special education; Teaching; Learning; Communication